TEACHER’S NONVERBAL IMMEDIACY BEHAVIORS AND STUDENTS’ MOTIVATION: A CORRELATIVE STUDY IN AN EFL CLASS IN CIKARANG - Kaniadewi, Nita; Shafira Larasati (Universitas PGRI Palembang, 2025)
This study explores the correlation between teachers' nonverbal immediacy behaviors and EFL students’ motivation at SMAN 1 West Cikarang. Using a quantitative correlational method, data were collected through questionnaires measuring both variables. Pearson’s Product-Moment Correlation Analysis revealed a positive relationship, with the correlation coefficient (ro = 0.54) exceeding the critical value (rt = 0.22) at a 0.05 significance level. Additionally, the t-test result (to = 5.785 > tt = 1.67) confirmed that the correlation was statistically significant. These findings indicate that teachers’ nonverbal immediacy such as gestures, eye contact, facial expressions, vocal tone, and physical presence plays an important role in enhancing students’ motivation to learn. Nonverbal communication helps create a supportive and engaging classroom atmosphere, making students feel more connected and enthusiastic about learning. Therefore, it is recommended that teachers consciously incorporate positive nonverbal behaviors in their teaching strategies to boost student motivation, especially in EFL contexts where emotional engagement is crucial for language acquisition.